Comparative Effectiveness of Website, Application, and Built-In Operating System Media in Digital Record Management Learning - Yuliansah Yuliansah; Peni Arumsari; Sutirman Sutirman; Riana Isti Muslikhah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Integrating technology into archival learning is essential for equipping vocational students with competencies aligned with the digital era. This study investigates the comparative effectiveness of three digital media—Windows Explorer (WE), Digital File Cabinet (DFC), and ERISE—in enhancing students’ knowledge and skills in archival practice. A post-test only control group experimental design was employed involving 214 students enrolled in an Archival Management course. Participants were randomly assigned to three groups: control (WE, n = 74), experimental group 1 (DFC, n = 74), and experimental group 2 (ERISE, n = 63). Data were collected using a 30-item multiple-choice test (targeting cognitive levels C2–C4; Cronbach’s Alpha = 0.65) and performance assessments using a rubric based on the 2023 National Competency Test. Statistical analysis included normality and homogeneity testing, followed by the Kruskal–Wallis test for group comparisons. Results revealed significant differences among the three groups in both knowledge and skill outcomes (p 0.001). ERISE and DFC yielded higher knowledge scores than WE, although all groups scored below 70. In terms of skills, ERISE and DFC outperformed WE, with mean scores above 75. The findings suggest that purpose-built digital platforms like ERISE and DFC are more effective than default operating system tools for archival learning. However, the low average knowledge scores highlight the need for instructional strategies that balance practical application with theoretical understanding.